Does it take the joints to stretch a mind? The ADHD and General Joint Hypermobility connection - Kacperczyk, Julia; Czyż, Witold; Wójcikiewicz, Michalina; Arczewski, Filip; Dziedzic, Karol; Kulbacka, Julia; Wojszczyk, Maciej; Zys, Damian; Pasek, Piotr; Ryniecka, Julia (Quality in Sport, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a childhood-onset neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity-impulsivity, or both, which negatively affect the quality of life for children and adults worldwide. ADHD is known to cause significant psychosocial distress, including academic failure, divorce, unemployment, and incarceration, and increases the risk of developing psychiatric disorders such as depression, anxiety, and substance abuse. While its cognitive and psychological impacts are yet well-documented, the implications of ADHD for physical health have only recently begun to receive increasing attention. Some of the known non-psychiatric health challenges associated with ADHD include obesity, autonomic dysregulation, musculoskeletal symptoms and joint hypermobility. This paper investigates recently discovered links between ADHD and symptoms of joint hypermobility, and focuses on the prevalence of generalized joint hypermobility, as well as ADHD comorbidity in connective tissue-related conditions, such as Ehlers-Danlos syndrome and hypermobility spectrum disorder.